Gender Stereotypes in Spanish- and English-Language Television Advertisements in the United States. Issue 3 (3rd May 2016) - Prieler, Michael
Abstract : This study analyzed 394 U.S. Spanish- and English-language television advertisements from 2013 for differences in gender representation. The findings indicate a high prevalence of gender stereotypes in both samples. For example, more women than men were depicted as young and were usually shown at home. Men actors were generally fully dressed, whereas women were often suggestively dressed. Voice-overs were clearly dominated by men, and product categories were stereotypically associated with gender. Despite allegedly more traditional Latina/o gender role attitudes in society, this study found little variation between Spanish- and English-language television advertisements in terms of gender stereotypes. The potential effects of such representations on audiences are discussed based on social cognitive theory and cultivation theory.